Welfare, equality and social justice: Scottish independence and the dominant imaginings of the 'New' Scotland. Issue 3 (2nd July 2016) - Mooney, Gerry; Scott, Gill
ABSTRACT: This paper focuses on the extent to which issues of equality, social justice and social welfare have been mobilised in the most prominent imaginings of an independent Scotland. Since 2011 the Scottish National Party (SNP) Scottish Government has repeatedly argued that any future independent Scotland will be characterised by a strong commitment to a distinctively Scottish social welfarism. This paper explores the main tenets of such claims noting that while the myths of Scottish distinctiveness in this respect have long been critiqued, they remain central to the visions of what Scottish society is, and what it could become. Drawing on specific framings and understandings of Scotland's past, leading SNP politicians have made claims that a new Enlightenment in Scotland could act as a 'beacon' for progressive policy-making across the rest of the UK and Europe. This new Enlightenment would be underpinned by the ethics of equality and social justice and the market and economic growth would be servants rather than drivers of social change. In critically exploring these claims to Scottish distinctiveness, this paper focuses on a particular area of social policy, childcare. It is argued that policy-making, as well as the SNP vision for the future, focus on areas of concern that have a lineage back to Enlightenment ideas – investing in childhood as a means to make a better society. It highlights the challenges of combining a market-driven childcare strategy with a social investment approach. The paper aims to promote a critical engagement with the unfolding 'imaginary' of any independent (or more devolved) Scottish society, a society in which a globally competitive economy can deliver important socially just goals.